PENGGUNAAN ALTMAN Z-SCORE, SPRINGATE, DAN ZMIJEWSKI DALAM MEMPREDIKSI KEBANGKRUTAN BUMN DI INDONESIA - Putri Arai; Nasrizal Nasrizal; Pipin Kurnia (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
This study aims to determine and analyze (1) the diffrences among Altman Z-Score, Springate, and Zmijewski models to predict bankruptcy, (2) the most accurate model to predict bankruptcy in State-owned Companies listed on the Indonesia Stock Exchange (IDX). The research method uses is a quantitative research method with secondary data in the form of financial reports during 2014-2018 accessed on www.idx.co.id and companies website. The population in this study are state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018 period. With the sample are 19 companies selected using purposive sampling method. The data analysis method using the Altman Z-Score, Springate, and Zmijewski formulas, with Microsoft Excel 2010 as a calculation tool. The results of this study is indicate that there are differences between the Altman Z-Score, Springate, and Zmijewski models in predict bankruptcy in state-owned companies listed on the IDX because each model uses different financial ratios. The most accurately model to predicts the bankruptcy of state-owned companies is the Zmijewski model.